Optimasi Jaringan Serat Optik menggunakan Metode Algoritma Genetika (Studi Kasus Unisma) - Diki Okiandri; Erni Yudaningtyas (Journal of Mechanical Engineering and Mechatronics, 2016)
Increased use of computers in education campus resulted in dense data traffic on communications networks. At the Islamic University of Malang (Unisma) there are more than 500 computers connected to the Internet using a wired media and hotspot access. Unisma existing network infrastructure in current use the Multimode Fiber Optic Backbone cable with static routing and Mesh topology. These lots number of users on the network resulting in dense data traffic that lead to long delays or long queues. Genetic algorithm is a search algorithm that is based on the natural genetic mechanism which also being used in optimizing network performance. This study compared the performance of existing network and a simulation of optimization using Genetic Algorithms. Measurement and retrieval of data consist of transfer time, also we built software engineering using visual studio program as a comparison model.The result of this study shows that optimization using genetic algorithm is able to find the fastest path and increase the speed of transmission of data packets by reducing transfer time by 53.5% and increase the datarate of 54.75% compared to the queuing method used on the existing network.